Refining Biomass Residues for Sustainable Energy and Bioproducts Technology, Advances, Life Cycle Assessment, and Economics - Kumar, R. Praveen; Gnansounou, Edgard; Raman, Jegannathan Kenthorai; Baskar, Gurunathan (Elsevier, AP, Academic Press, 2020)
Refining Biomass Residues for Sustainable Energy and Bioproducts: Technology, Advances, Life Cycle Assessment and Economics is a one-stop reference on the biorefinery of various kinds of residue and waste feedstock for the sustainable production of biofuels and biochemicals. Written by a team of global experts, this book introduces the concept of integrated biorefinery systems for waste management, as well as their operation and feedstock sourcing. It explores the specificities, current developments and potential end-products of various types of residue, from industrial and municipal, to agricultural and marine, also discussing residue from food industries. Finally, global case studies examine successful experiences in different regions.Practitioners and consultants in the biorefinery, bioenergy and biochemicals sector, as well as those working on waste management will benefit from this book's well-structured content on the types of waste they may encounter, their processing and pre-processing requirements, possible end-products, and cost and sustainability aspects.- Covers biofuel production, waste management and sustainable development for various types of waste such as industrial waste, agricultural waste, food waste, municipal solid waste and marine waste.- Includes a Life Cycle Assessment of waste biorefinery models, costs and market analysis.- Written by an international team of authors and presents case studies from around the world
Approx. 200 illustrations
Part I: Concept of integrated biorefinery systems for waste management 1. Solid Waste Biorefineries; Part II: Sources and operation of waste biorefineries 2. Bacterial production of Fatty acid and Biodiesel: Opportunity and challenges 3. Microbial derived natural bioproducts for a sustainable environment: A bio-perspective for Waste to Wealth 4. Application of Heterogeneous Acid catalyst derived from biomass for biodiesel process intensification: A comprehensive review 5. Sources and operation of waste biorefineries 6. A biorefinery approach towards the production of renewable platform chemicals from sustainable biomass 7. Microalgae biomass production for a biorefinery system: Recent advances and the way towards sustainability; Part III: Industrial waste biorefineries 8. Generation of Bioenergy from industrial waste using Microbial Fuel Cell Technology for the sustainable future 9.
- Assessment of Crude Glycerol Utilization for Sustainable Development of Biorefineries ; Part IV: Agroindustry waste biorefineries 10. Sweet sorghum: A future potential resource for bioenergy production 11. Agro-residue based biorefineries 12. Effective utilization of sugarcane thrash for energy production 13. Potentials of Post harvest Rice crop residues as a source of Biofuel 14. Pretreated Empty Fruit Bunch by ozonolysis for synthesis of carboxymethyl cellulose, levulinic acid and levulinic ester 15. Bio-energy generation from agricultural wastes and enrichment of end products 16. Argo-Industry wastes: Feedstocks for biofuels and biomaterials for sustainable rural development; Part V: Food Industry waste biorefineries; 17. Food industry waste biorefineries: Future energy, valuable recovery and waste treatment 18. Food industry waste biorefineries 19. Processing food waste for production of platform chemicals; Part VII: Marine waste biorefineries 20. Marine waste biorefineries 21.
- Blue Biotechnology: A Vision for Future Marine Biorefineries 22. Marine waste biorefineries; Part VIII: Life Cycle Assessment of waste biorefinery models 23. Comparative Life Cycle Analysis of synthetic detergents and biosurfactants - an overview 24. Life cycle assessment, technical and economical analysis of jatropha biodiesel; Part IX: Economics and cost analysis of waste biorefineries 25. Economics and cost analysis of waste biorefineries 26. Process Design, Techno-Economic and Life Cycle Assessments of selected Sugarcane-Based Biorefineries: A case study in the South African context